2021
DOI: 10.1097/fjc.0000000000000987
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Direct Oral Anticoagulants Versus Warfarin for Intracardiac Thromboses

Abstract: Intracardiac thrombus (ICT) formation is a common complication of several cardiovascular diseases. Warfarin is recommended for treatment of ICT by guidelines based on observational studies occurring before the advent of nonvitamin K antagonist direct oral anticoagulants (DOACs). We aim to evaluate the current prescribing patterns at our institution and to compare the efficacy and safety profiles of warfarin versus DOACs for ICT. This is a retrospective review of adult patients treated with oral anticoagulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 23 publications
3
39
0
Order By: Relevance
“…In aspects of our key findings, patients who received NOACs had a greater resolution more than 1 time than those with VKAs or APT, which was consistent with several articles [ 12 , 26 ]. Researchers have explored the effectiveness of NOACs in the treatment of VT. Sedhom et al collected 85 cases of direct oral anticoagulants for treatment of left VT. 74 patients (87%) were prescribed an NOAC and 93.2% of them had a complete resolution (69/74) [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In aspects of our key findings, patients who received NOACs had a greater resolution more than 1 time than those with VKAs or APT, which was consistent with several articles [ 12 , 26 ]. Researchers have explored the effectiveness of NOACs in the treatment of VT. Sedhom et al collected 85 cases of direct oral anticoagulants for treatment of left VT. 74 patients (87%) were prescribed an NOAC and 93.2% of them had a complete resolution (69/74) [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…In a retrospective study including 101 patients with left VT, 41 (40.6%) received NOACs and 60 (59.4%) received VKA at 1-year follow-up, and the NOACs group had a faster and earlier thrombolysis rate than VKA (82% versus 64.4%), a similar rate of thromboembolism (5% versus 2.4%, p = 0.388), and a lower incidence of bleeding events (0% versus 6.7%, p = 0.03) [ 26 ]. Another study also found that the time of thrombus resolution in the NOACs group was faster than that in the VKAs group (63 days [IQR 40, 138] versus 123 days [IQR 86, 244], p = 0.003) [ 12 ]. Bass et al 2021 retrospectively included 949 patients diagnosed with left VT; 180 (19%) received NOACs and 769 (81%) received warfarin, and no differences in new embolism or bleeding events were observed (NOACs versus warfarin: 7.8% versus 11.7%, p = 0.13; 10.9% versus 7.8%, p = 0.40) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations